CONCEPTUAL AND POLITICAL ASPECTS OF ENSURING THE ECOLOGICAL SAFETY OF THE SOCIETY - Hayitov Jurabek (Scholar Express Journals, 2023)
In this article, based on the need to achieve stability in the context of globalization processes in the world, political directions for eliminating ecological risks and ensuring ecological safety in this process are revealed.
Keywords: globalization; integration; ecological crisis; international community